Facile synthesis of hierarchical pore foam catalysts with Brønsted–Lewis acid sites for the one-pot conversion of cellulose to 5-hydroxymethylfurfural. Issue 84 (26th August 2016) - Shen, Yating; Zhang, Yunlei; Zhu, Enwei; Chen, Yao; Jin, Pei; Liu, Meng; Yan, Yongsheng; Li, Chunxiang
Abstract : The Whole process of synthesis of HPFCs by Pickering high internal phase emulsions and application in conversion of cellulose to HMF. Abstract : Herein, hierarchical pore foam catalysts (HPFCs) containing Brønsted–Lewis acidic sites and with hierarchical porous properties were synthesized, and their catalytic performance was applied to convert cellulose into HMF through a one-pot reaction. Sulfated ZrO2 nanostructures (SZs) were synthesized through grafting ZrO2 onto the surface of mesoporous silica nanoparticles, and superacid was further introduced onto the surface of the ZrO2 shells through sulfuric acid treatment and calcination. The representative SZs firstly acted as stabilizers in the synthesis of oil-in-water (O/W) Pickering high internal phase emulsions (Pickering HIPEs). After a subsequent ion-exchange process, Brønsted acidic sites were located on the surface of HPFCs. The resulting HPFCs exhibit advantageous properties for catalysis, such as favorable meso–macro porosity, strongly acidic surfaces, and structural stability. Compared with other catalysts ( e.g., one without superacid and mesopores (HPFCs-1) and another (HPFCs-2) without mesopores), HPFCs-3 manifested more efficiently (42%) the production of 5-hydroxymethylfurfural (HMF) from cellulose. This study develops a promising method for the fabrication of specific functional solid catalysts, which can be applied to the value-added conversion of abundant cellulose.